(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article presents information on diseases affecting the distal parts of the limbs in cattle, fousing on the polyetiological causes of hoof diseases. Hoof diseases are widespread among cattle, making the study of their etiopathogenesis highly significant. The rsearch emphasizes the importance of understanding these conditions for effective treatment and prevention strategies.